Data sharing as a prerogative and as challenge for genomics in personalised health. (20th October 2021) - Becker, R
Abstract: Without data sharing, the approach of personalised healthcare will not work - from secondary opinions to finding similar patients to compiling a reference genome to research. The more data are being used and the more difficult it is as well to anonymise data, where this is ultimately impossible for genomic data related to a person, the more challenges are faced with regard to the privacy and legal frameworks. There is the need for effective arrangements for data-sharing across different institutions, communities, and contexts. There are different legal frameworks around processing health and genetic data across Europe and, there is a difficulty to share data outside the EU in general, which often hampers the data sharing despite the willingness of people to make their data available. It is important to develop common principles and legal frameworks that enable sharing of patient-level data for research in a way that is ethical and acceptable to patients and the public.